The Perceptions Of Healthcare Managers On Green Human Resource Management Practices And Their Relationship To Work Values In Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
Background: Green human resources management (GHRM) is the alignment of established human resource practices with environmental goals and policies. Integrating sustainable practices has become crucially important as healthcare facilities deal with growing environmental issues.The study aimed: To assess the perceptions of healthcare managers (HCMs) on Green Human Resource Management practices (GHRMP) and their relationship to work values.Methods: A descriptive correlational research design was used in five Hospitals, Jeddah, Saudi Arabia. All healthcare managers which consider a convenience sample of healthcare managers who were working at Hospitals during the period of data collection. Three tools: personal data, Green Human Resource Management Practices Scale, and Work Value Questionnaires were used to collect data needed for the current study.Results: According to the study's findings, a significant portion of hospital HCMs gave "low" answers to the GHRMP dimensions; also, over two-thirds of HCMs demonstrated low levels of work values. Conclusion: There is a statistically significant positive association between the study participants' overall work values and their total GHRMP. Healthcare managers' roles and objectives should be defined in a green manner, and evaluations should incorporate some green outcomes. Green performance indicators should be used in the evaluation and performance management system.